dy/dx+4xy=e^-2x & y(0)=1
in Algebra 2 Answers by Level 12 User (101k points)

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

34 Answers

Let Y,h: Y'h+4xy,h=0
by Level 12 User (101k points)
→ {dY,h/Y,h={-4xdx
by Level 12 User (101k points)
→lny,h=-2x^2+c ~upper
by Level 12 User (101k points)
Y,h=c•e^-2x^2
by Level 12 User (101k points)
Now if F_=F(x):
by Level 12 User (101k points)
Y=F•e^-2x^2 ,
by Level 12 User (101k points)
Y'=(F'-4xF)e^-2x^2
by Level 12 User (101k points)
And by substitution to the given:
by Level 12 User (101k points)
F'=e^2x^2-2x
by Level 12 User (101k points)
F=c+{e^2x^2-2x dx
by Level 12 User (101k points)
Therefore: y=e^-2x^2•(c+{e^2x^2-2x dx) →(1)
by Level 12 User (101k points)
We know that, e^w= ∞summation lower n=0 w^n/n!
by Level 12 User (101k points)
W_=2x^2
by Level 12 User (101k points)
e^2x^2=1+2x^2+4x^4/2! +8x^6/3! +... →(2)
by Level 12 User (101k points)
W_= -2x
by Level 12 User (101k points)
e^-2x=1-2x+4x^2/2! -8x^3/3! +—... →(3)
by Level 12 User (101k points)
Then e^2x^2-2x
by Level 12 User (101k points)
=e^2x^2•e^-2x
by Level 12 User (101k points)
100"9=90 n_2     how to get this answer  explain each detail ?       I'm not at school today!
by
=1+s(x)
by Level 12 User (101k points)
Where s(x) is an infinite polynomial of the form:
by Level 12 User (101k points)
∞ summation n=0 Kx^n
by Level 12 User (101k points)
That is, there is not a constant term.
by Level 12 User (101k points)
Therefore the integral in (1) is
by Level 12 User (101k points)
{(1+s) dx
by Level 12 User (101k points)
=x+{s(x) dx
by Level 12 User (101k points)
=x+r(x)
by Level 12 User (101k points)
Now r(x) has not also any constant term,
by Level 12 User (101k points)
Thus r(0)=0
by Level 12 User (101k points)
Then (1)becomes y(x)=e^-2x^2•(c+x+r(x))
by Level 12 User (101k points)
→y(0)=e°•(c+0+0)_=1
by Level 12 User (101k points)
→ c=1
by Level 12 User (101k points)
Therefore the solution to the initial condition problem is given by,
by Level 12 User (101k points)
y(x)=e^-2x^2•[1+{(EXP with ^upper(2x^2-2x))dx]
by Level 12 User (101k points)

Related questions

1 answer
asked Feb 28, 2015 in Pre-Algebra Answers by lovelymath Level 2 User (1.9k points) | 942 views
1 answer
asked May 12, 2013 in Calculus Answers by anonymous | 935 views
5 answers
asked Jan 7, 2014 in Algebra 2 Answers by Jennifer A. Cascaño Level 12 User (101k points) | 824 views
9 answers
13 answers
14 answers
asked Jan 10, 2014 in Algebra 1 Answers by Jennifer A. Cascaño Level 12 User (101k points) | 1.6k views
1 answer
asked Oct 8, 2020 in Calculus Answers by anonymous | 1.2k views
20 answers
asked Jan 30, 2014 in Calculus Answers by Jennifer A. Cascaño Level 12 User (101k points) | 2.1k views
25 answers
16 answers
3 answers
asked Jan 18, 2014 in Algebra 2 Answers by Jennifer A. Cascaño Level 12 User (101k points) | 2.7k views
37 answers
asked Feb 6, 2014 in Calculus Answers by Jennifer A. Cascaño Level 12 User (101k points) | 4.5k views
12 answers
asked Jan 12, 2014 in Algebra 2 Answers by Jennifer A. Cascaño Level 12 User (101k points) | 1.3k views
1 answer
asked Feb 14, 2014 in Calculus Answers by Jennifer A. Cascaño Level 12 User (101k points) | 1.2k views
40 answers
asked Jan 30, 2014 in Calculus Answers by Jennifer A. Cascaño Level 12 User (101k points) | 4.1k views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
87,548 questions
99,681 answers
2,417 comments
465,800 users